Pakistan’s water resource management: Ensuring water security for sustainable development - Ishaque, Waseem; Mukhtar, Mudassir; Tanvir, Rida (Frontiers in Environmental Science, 2023)
Pakistan is blessed with abundant water resources but facing a critical water shortage due to a lack of storage facilities, poor water governance, and the adverse impacts of climate change. The burgeoning population at present 225 million, which is expected to cross 250 million by 2025 is creating an additional burden on water resources, as per capita availability is depleting sharply from 5000 m3 in 1951 to 1100 m3 in 2005, which is expected to fall to 800 m3 by 2025. Pakistan’s water demand is increasing at an average yearly rate of 10% which in terms of the area will increase to 338 km3 by 2025, against the availability of 240 to 258 km3. Out of the available surface water, approximately 74% is extracted, while 83% of the groundwater is used for agricultural and other uses, which is an exceptionally high ratio for a water-scarce country like Pakistan. The adverse impacts of climate change are also causing extreme weather conditions, resulting in drought and floods almost every year. Inadequate water reservoirs, water wastage in agriculture and households, negligible wastewater recycling, and contamination of drinking water are causing health risks that have turned serious national security challenges for Pakistan. This research article argues that surface and subsurface water in Pakistan is depleting sharply, and if not addressed in time, has the potential of becoming the biggest national security problem. The article investigates the available water status in Pakistan covering surface and subsurface resources in detail, including reservoirs for storage, and sectoral utilization, to draw conclusions on water availability and usage requirement. The policy recommendations highlight the effective integration of smart technology in addressing multidimensional water issues and efficient water governance for ensuring water security for the sustainable development of Pakistan.